Ionizing radiation and volumetric mammographic density - Beata Pepłońska; Mateusz Mirowski; Paweł Kałużny; Joanna Domienik-Andrzejewska (International Journal of Occupational Medicine and Environmental Health, 2022)
Objectives Mammographic density (MD) refers to the percentage of dense tissue of an entire breast and was proposed to be used as a surrogate marker for breast cancer. High-dose ionizing radiation (IR) has been recognized as a breast cancer risk factor. The aim of our study was to investigate association between lifetime low dose ionizing radiation (LDIR) and MD.